Performance Of Viterbi Based Detectors For Wideband Mobile Radio Channels - Muhayiddin, Mohd. Nazri (2002)
The focus of the thesis is to study the performance of outdoor wideband mobile radio systems operating at data rates of 144 kbits/s and 384 kbit/s standardised by ITU for users in fast vehicular and walking-speed pedestrian environment respectively.